Preventing Loss of Basic Activities of Daily Living and Instrumental Activities of Daily Living in Elderly: Identification of Individual Risk Factors in a Holistic Perspective. Issue 5 (September 2015) - Candela, Filippo; Zucchetti, Giulia; Ortega, Enrique; Rabaglietti, Emanuela; Magistro, Daniele
Abstract : This study investigated the association between physical functioning and activities of daily living (ADL) of elderly people, taking into account the role of cognitive, psychological, and social factors. We administered physical, cognitive, psychological, and social instruments to investigate the level of basic and instrumental activities of daily living (BADL and IADL). The analysis showed that physical functioning was the only individual factor that was significantly linked with the level of BADL and IADL. This study underlines that physical functioning is the main individual characteristic directly associated with the level of BADL and IADL in old age.